SELAYANG PANDANG GERAKAN POLITIK & PERUBAHAN SOSIAL (Kajian Sosiologis Perilaku Makna) - Bambang Amir Alhakim (Jurnal Cakrawala Ilmiah, 2023)
Political movements are usually initiated by dissatisfaction with a large system in every social function. When this function experiences deviation (distortion), conflict occurs which triggers political movements. With the aim of normalizing towards social change.Conflict is triggered by social inequality (social injustice), as a trigger for a social movement towards social change. In a theoretical perspective, conflict is viewedas an initial indication of a social (political) movement. This social scientific article examines the meaning of behavior in sociological studies from the perspective of the meaning of behavior in the occurrence of political movements aimed at better social change.